Ethnobotanical study of medicinal plants in Torul district, Turkey (Bangladesh Journal of Plant Taxonomy, 2019)
This study is aimed at reporting some of the plants traditionally used in the treatment of diseases by the local people living in the centre of Torul district and its surrounding villages. A face-to-face two-part questionnaire survey was conducted with 82 local people. Identification of 29 taxa belonging to 18 families has been confirmed and their medicinal uses have been recorded. In addition, the usage patterns of plant parts andpurposes are recognized. Plants are mostly used in the treatment of cold and flu, stomach disorders, gynecological, cardiovascular, and respiratory diseases. The highest use value (UV) was recorded for Rosa canina (0.54) and Mentha longifolia subsp. longifolia (0.46) and the highest Informants Consensus Factor (FIC) was cited for cold and flu (0.83) followed by stomach disorders (0.75). New information for folklore medicines have been collected from the study area.